Structure of the Parainfluenza Virus 5 (PIV5) Hemagglutinin-Neuraminidase (HN) Ectodomain - Welch, Brett D.; Yuan, Ping; Bose, Sayantan; Kors, Christopher A.; Lamb, Robert A.; Jardetzky, Theodore S. (PLoS pathogens, 2013)
Paramyxoviruses cause a wide variety of human and animal diseases. They infect host cells using the coordinated action of two surface glycoproteins, the receptor binding protein (HN, H, or G) and the fusion protein (F). HN binds sialic acid on host cells (hemagglutinin activity) and hydrolyzes these receptors during viral egress (neuraminidase activity, NA). Additionally, receptor binding is thought to induce a conformational change in HN that subsequently triggers major refolding in homotypic F, resulting in fusion of virus and target cell membranes. HN is an oligomeric type II transmembrane protein with a short cytoplasmic domain and a large ectodomain comprising a long helical stalk and large globular head domain containing the enzymatic functions (NA domain). Extensive biochemical characterization has revealed that HN-stalk residues determine F specificity and activation. However, the F/HN interaction and the mechanisms whereby receptor binding regulates F activation are poorly defined. Recently, a structure of Newcastle disease virus (NDV) HN ectodomain revealed the heads (NA domains) in a "4-heads-down" conformation whereby two of the heads form a symmetrical interaction with two sides of the stalk. The interface includes stalk residues implicated in triggering F, and the heads sterically shield these residues from interaction with F (at least on two sides). Here we report the x-ray crystal structure of parainfluenza virus 5 (PIV5) HN ectodomain in a "2-heads-up/2-heads-down" conformation where two heads (covalent dimers) are in the "down position," forming a similar interface as observed in the NDV HN ectodomain structure, and two heads are in an "up position." The structure supports a model in which the heads of HN transition from down to up upon receptor binding thereby releasing steric constraints and facilitating the interaction between critical HN-stalk residues and F.